ANALISIS PENGARUH KOMPETISI INDUSTRI TERHADAP PENGUNGKAPAN SEGMEN OPERASI PERUSAHAAN - Muhammad Naufal Noor Hakim; Tarmizi Achmad (Diponegoro Journal of Accounting, 2020)
The purpose of this study to analyse and provide empirical evidence regarding relationship between industry competition and operating segment disclosure, with firm size, leverage, and profitability as control variables, based on proprietary cost theory stated by Verrecchia that in the absence of these costs, companies are incentive to voluntarily disclose relevant information to the market in order to reduce information asymmetry. Consistent with previous research that the level of segment disclosure will be tested using a disclosure index based on the mandatory requirement of Pernyataan Standar Akuntansi Keuangan (PSAK) 5 Revised 2009 operating segments. Data of this study were obtained from financial and annual report that drawn from Indonesian Stock Exchange (IDX) site. The population in this study was 135 manufacture companies registered from 2011 to 2015. The sampling method in this study using purposive sampling method and obtain 434 final sample. The analytical tool in this study is multiple regression analysis and one way annova. The results show that the average level of disclosure of operating segments manufacture companies listed on Indonesian Stock Exchange in 2011 to 2015 was 59,3% ranging from 20,8% to 91,7%. The results of this stud found that industry competition, company size, leverage, and profitability had a positive significant relationship to company’s operating segments disclosure, but in one way annova found that companies with lowest competition industry made higher disclosure of operating segments compared to highest competition industry. This results can certainly give description that operating segment disclosure influenced by the characteristics that are used as variables in this study.